2010
DOI: 10.2146/ajhp090153
|View full text |Cite
|
Sign up to set email alerts
|

Developing and implementing clinical decision support for use in a computerized prescriber-order-entry system

Abstract: Through an interdisciplinary collaboration, an academic health care system planned, designed, and implemented institution-specific, CPOE-integrated CDS to improve clinical efficiency and facilitate the compliance with regulatory policies and guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…We have demonstrated that postimplementation tracking and iterative changes to a deployed CDS can result in a 4.5-fold increase in adoption rate. Similar mechanisms have been implemented to track effectiveness of CDS; Zimmerman et al devised monthly reports on alert occurrence and override rates organized into a dashboard view [39]. Using post-implementation tracking methods such as this allows for development of novel metrics for predicting inappropriate alerts and responses.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that postimplementation tracking and iterative changes to a deployed CDS can result in a 4.5-fold increase in adoption rate. Similar mechanisms have been implemented to track effectiveness of CDS; Zimmerman et al devised monthly reports on alert occurrence and override rates organized into a dashboard view [39]. Using post-implementation tracking methods such as this allows for development of novel metrics for predicting inappropriate alerts and responses.…”
Section: Discussionmentioning
confidence: 99%
“…Adoption of these systems may offer many institutional benefits including reduced test turn-around time (TAT), improved test usage, and better adherence to practice guidelines 14–19. Specifically, these systems may alert physicians to test-specific inappropriate ordering, provide alternative tests to consider, list cost information, and suggest order sets for bundled ordering 15 20. Use of CPOE alert systems have been shown to improve ordering of certain tests including cardiac markers in certain appropriate situations,21 as well as to improve compliance with the American Heart Association guidelines for cardiac monitoring 22.…”
Section: Introductionmentioning
confidence: 99%
“…During CPOE implementation, decisions need to be made about the numerous configuration options that affect the manner in which clinicians work, how the system functions, and, potentially, the clinical outcome of patient experiences. 9,14 While the optimal configuration of CPOE is unclear, the failure to consider sitespecific characteristics and workflow when configuring a CPOE system is a potential cause of unintended consequences. 13,15,16 Evidence-based standardization could dramatically reduce the financial and human resources needed for implementation of these systems, especially if vendor CPOE systems are preconfigured accordingly.…”
mentioning
confidence: 99%
“…These methods are discussed in greater detail elsewhere. 14,22 Standards and certifications. Complicating the matter of configuring optimal CDS alerting methods are CPOE and CDS standard-setting initiatives by government and private organizations.…”
mentioning
confidence: 99%